(untitled) (Acta Horti Botanici Bucurestiensis, 2025)
A priority for the states of the European Union is the identification of invasive and potentially invasive alien species, their main routes of entry and spread, and the impact they have on various types of habitats. The aim of this study was to contribute to the knowledge of hotspots (areas with a large number of invasive species) or those where their abundance-dominance is very high and produces a major impact on native vegetation. Through the research carried out on invasive and potentially invasive alien species in Mureș County, 1204 records made in 168 locations in Mureș County were analyzed and 31 species of invasive alien plants were identified, of which three species are of concern for the European Union, namely: Asclepias syriaca, Ailanthus altissima și Impatiens glandulifera. In the study area, the species with the highest presence are: Erigeron annuus subsp. anuus identified in 248 points, Xanthium orientale subsp. italicum (201 points), Robinia pseudoacacia (142 points), Solidago canadensis (83 points), Erigeron canadensis and Reynoutria japonica (each with 74 points), and Ambrosia artemisiifolia (67 points). In the observation points, up to 4-6 species of invasive plants grouped in the same type of habitat were found. These were generally habitats subject to strong anthropogenic impact, roadsides, fallows, abandoned lands, and agricultural crops. Each identified species was analyzed from the chorological point of view, the bioforms, the ways and the purpose of their introduction, and the phytogeographical elements.